Three‐Year Outcomes of Recovery of Erectile Function after Open Radical Prostatectomy with Sural Nerve Grafting. (1st August 2014) - Siddiqui, Khurram M.; Billia, Michelle; Mazzola, Clarisse R.; Alzahrani, Ali; Brock, Gerald B.; Scilley, Christopher; Chin, Joseph L.
Abstract: Introduction: Optimal oncologic control of higher stage prostate cancers often requires sacrificing the neurovascular bundles (NVB) with subsequent postoperative erectile dysfunction (ED), which can be treated with interposition graft using sural nerve. Aims: To examine the long term outcome of sural nerve grafting (SNG) during radical retropubic prostatectomy (RRP) performed by a single surgeon. Methods: Sixty‐six patients with clinically localized prostate cancer and preoperative International Index of Erectile Function (IIEF) score >20 who underwent RRP were included. NVB excision was performed if the risk of side‐specific extra‐capsular extension (ECE) was >25% on Ohori' nomogram. SNG was harvested by a plastic surgeon, contemporaneously as the urologic surgeon was performing RRP. IIEF questionnaire was used pre‐ and postoperatively and at follow‐up. Main Outcome Measures: Postoperative IIEF score at three years of men undergoing RRP with SNG. Recovery of potency was defined as postoperative IIEF‐EF domain score >22. Results: There were 43 (65%) unilateral SNG and 23 (35%) bilateral SNG. Mean surgical time was 164 minutes (71 to 221 minutes).The mean preoperative IIEF score was 23.4+1.6. With a mean follow‐up of 35 months, 19 (28.8%) patients had IIEF score >22. The IIEF‐EF scores for those who had unilateral SNG and bilateral SNG were 12.9+4.9 and 14.8+5.3 respectively. History of diabetes ( P = 0.001) and age ( P =0.007) negatively correlated with recovery of EF. 60% patients used PDE5i and showed a significantly higher EF recovery (43% vs. 17%, P = 0.009). Conclusions: SNG can potentially improve EF recovery for potent men with higher stage prostate cancer undergoing RP. The contemporaneous, multidisciplinary approach provides a good quality graft and expedited the procedure without interrupting the work‐flow.